Improving Critical Thinking Skills and Learning Outcomes through the Implementation of the Inquiry Learning Model in Social Studies - Salamah Salamah; Dian Aprianti S; Anung Pramudyo; Victor Novianto (UM Purwokerto Press, 2023)
This study aimed to identify the application of the inquiry learning model in improving (1) critical thinking skills, and (2) learning outcomes in Social Studies of grade VIII A students at State Junior High School 1 Girimulyo Kulon Progo in 2021/2022 school year. This was a classroom action research consisting of 2 cycles with 3 meetings of each. Subjects involved students at State Junior High School 1 Girimulyo Kulon Progo in the 2021/2022 school year. Data were gathered from observations, test learning outcomes, and, documentation. Qualitative data and quantitative data data were analyzed by using descriptive statistical analysis. Results showed that the learning inquiry model applied was able to improve students' (1) critical thinking skills reached 80% excellent category indicated at pre-cycle, cycles I and II with class score averages of 55.40 (45,16%), 67.00 (61,29%) and 86.61 (80,65%) at lower, good and very good categories, respectively, (2) learning outcomes in Social Studies subjects 80% of students reach KKM = 751 indicated at pre-cycle for Daily Test 1 and 2 with score averages of 62,26 (19,35%) and 63,87 (22,58%) at not mastery and not mastery categories, respectively, at cycles 1 and 2 with class score averages of 73.55(58,06%) and 80.00 (90).